Primary Angiitis of the Central Nervous System: Magnetic Resonance Imaging Spectrum of Parenchymal, Meningeal, and Vascular Lesions at Baseline. Issue 5 (May 2017) - Boulouis, Grégoire; de Boysson, Hubert; Zuber, Mathieu; Guillevin, Loïc; Meary, Eric; Costalat, Vincent; Pagnoux, Christian; Naggara, Olivier
Abstract : Background and Purpose—: Primary angiitis of the central nervous system remains challenging. To report an overview and pictorial review of brain magnetic resonance imaging findings in adult primary angiitis of the central nervous system and to determine the distribution of parenchymal, meningeal, and vascular lesions in a large multicentric cohort. Methods—: Adult patients from the French COVAC cohort (Cohort of Patients With Primary Vasculitis of the Central Nervous System), with biopsy or angiographically proven primary angiitis of the central nervous system and brain magnetic resonance imaging available at the time of diagnosis were included. A systematic imaging review was performed blinded to clinical data. Results—: Sixty patients met inclusion criteria. Mean age was 45 years (±12.9). Patients initially presented focal deficit(s) (83%), headaches (53%), cognitive disorder (40%), and seizures (38.3%). The most common magnetic resonance imaging finding observed in 42% of patients was multiterritorial, bilateral, distal acute stroke lesions after small to medium artery distribution, with a predominant carotid circulation distribution. Hemorrhagic infarctions and parenchymal hemorrhages were also frequently found in the cohort (55%). Acute convexity subarachnoid hemorrhage was found in 26% of patients and 42% demonstrated pre-eminent leptomeningeal enhancement, which is found to be significantly more prevalent in biopsy-proven patients (60% versus 28%; P =0.04). Seven patients had tumor-like presentations. Seventy-seven percent of magnetic resonance angiographic studies were abnormal, revealing proximal/distal stenoses in 57% and 61% of patients, respectively. Conclusions—: Adult primary angiitis of the central nervous system is a heterogenous disease, with multiterritorial, distal, and bilateral acute stroke being the most common pattern of parenchymal lesions found on magnetic resonance imaging. Our findings suggest a higher than previously thought prevalence of hemorrhagic transformation and other hemorrhagic manifestations. Abstract : Supplemental Digital Content is available in the text.